Flora of Danau Dusun Besar conservation forest in Bengkulu Province, Indonesia - WIRYONO WIRYONO; Rohidin Mersyah; Mariska Tarantona (Society for Indonesian Biodiversity, 2020)
Abstract. Wiryono Mersyah R, Tarantona M. 2020. Flora of Danau Dusun Besar conservation forest in Bengkulu Province, Indonesia. Biodiversitas 21: 5640-5649. Few studies on flora of freshwater swamp forest in Sumatra have been published and accessible online. This study aimed to assess the composition and diversity of plant species and to describe the dominant species in conservation forest of Danau Dusun Besar Nature Reserve and Nature Tourism Park in Bengkulu which consists mostly of freshwater swamp forests and a lake. Data collection was done using a combination of quantitative methods with systematic plots and qualitative methods through observation. The quantitative data were analyzed to determine indexes of diversity, evenness and importance value. This study recorded 23 species of trees with diversity index (H?) and evenness index (E) of 0.29 and 0.09, respectively, and recorded 136 species of shrubs and herbs with H? and E values of 3.68 and 0.75, respectively. The most dominant species of trees was Alstonia spatulata, of shrubs and herbs Stenochlaena palustris. The small diameter class of trees and the covering of trees with climbers indicated that the large trees had been cut. We recommend further studies with more and better-located plots to get better data on the vegetation composition and structure, including the invasion of alien species Ludwigia peruviana and the effect of climbers on trees.